ANALYSIS OF THE STRUCTURAL PERFORMANCE OF THE UPPER STRUCTURE OF THE JAGAKARSA JAKARTA SELF-APARTMENT BUILDING USING ETABS SOFTWARE WITH PUSHOVER ANALYSIS METHOD - Jujun Junaedi Hidayat; Sempurna Bangun; Kristina Sembiring; Pio Ranap Tua Naibaho (International Journal of Civil Engineering and Infrastructure, 2025)
An earthquake is a natural disaster event that causes seismic waves and vibrations or shocks due to a sudden release of energy under the earth's surface. Earthquakes are caused by collisions or frictions between tectonic plates (earth plates) or the collapse of gaps in the sea. In this study, it is specialized to evaluate the performance of the upper structure by adopting a plan on the existing building structure (existing condition) in accordance with the change in the field due to differences, changes in field conditions and will carry out a non-linear static analysis in the form of pushover analysis using the ATC-40 method with a building that functions as a flat. The results of the pushover analysis in the Rusun Jagakarsa building by modeling using the ETABS application obtained a greater value from the base shear in the y direction compared to the base shear in the x direction. The capacity curve in the x-direction stopped at step 9 with a value from the Base Shear of 48.654,4992 KN, the capacity curve in the direction of y stopped at step 3 withand a Base Shear value of 29.656,6413 KN. The level of performance of the structure was measured based on the calculation of the maximum parameter of total drift and the maximum parameter of inelastic drift of the direction x of 0.00803 < 0.01 value is included in Damage Control (DC). For the maximum parameter value of the total drift resulting from the calculation of pushover in the direction y is 0.00741 < 0.01, based on these results it is included in the category of Immediate Occupancy (IO). Then for the maximum parameter value of inelastic drift as a result of the calculation of Pushover in the direction of y is 0.00745 > 0.005, this value is included in the category of Damage Control (DC).Keywords: Earthquake, pushover, ETABS